Proyecto de factibilidad para la creación de una empresa productora y comercializadora de chifles, ubicada en la parroquia Moraspungo a partir del año 2013 - Loor Mora, Neida Karina (2013)
The feasibility study carried out in the project called installation of a manufacturer and marketer of chifles in Moraspungo presented positive results for implementing the project, this is proved by the market research carried out to the residents and merchants of the Parish Moraspungo in business chifles consumption. Also economic study threw a low investment of banana chips processing plant, with the financial evaluation demonstrating high profitability and liquidity of the business to install and has also shown a high cost benefit. The business will be installed with the help of a personal contribution and a bank loan. Important aspects to be considered in the project, as appropriate chifle marketing in the Parish Moraspungo and parishes and townships closest advantage of the existence of a large unmet demand through strategies for product launch and ensure adequate market segmentation favorable to the project. The project outlines, in its first part the introduction, and the problematization, continuing with setting goals and assumptions, all acoderado with a good theoretical basis. Subsequent chapters mention the result of the survey and the economic and financial studies., Which were crucial to the successful implementation of the project envisioning an excellent return and benefit to the inhabitants of Moraspungo, giving thrust socioeconomic Moraspungo this Parish, located in the center of the province of Cotopaxi.